Risk of bleeding following double balloon enteroscopy in patients on continued antiplatelet and/or anticoagulation therapy - Zaver, Himesh B.; Ghoz, Hassan; Stancampiano, Fernando; Alnahhal, Khaled I.; Malviya, Balkishan; Patel, Krupa; Rodriguez, Andrea C.; Oberoi, Mansi; Koralewski, Andrea; Crawford, Matthew J.; Choudhry, Aruj; Mareth, Karl; Werlang, Monia E.; Kroner, Paul T.; Simons-Linares, C. Roberto; Lukens, Frank; Bartel, Michael J.; Stark, Mark; Brahmbhatt, Bhaumik (Endoscopy International Open, 2021)
Background and study aims Anticoagulation (AC) and antiplatelet (AP) therapy may increase the risk of gastrointestinal bleeding after double balloon enteroscopy (DBE); however, limited data are currently available regarding the incidence. The aim of this study was to assess the incidence and clinical characteristics of post-DBE bleeding in patients on AC and AP therapy.Patients and methods The medical records of patients who underwent DBE between 2009 and 2013 at Mayo Clinic, Florida, were retrospectively reviewed. Patients were divided into three groups: 1) continued AP therapy; 2) AC therapy; and 3) neither AP nor AC at the time of DBE. Follow-up data were collected at 60 days and 1 year.Results A total of 683 patients were identified; 43 on AC, 183 on AP and 457 not on AP or AC therapy. The most common indication for DBE was obscure gastrointestinal bleeding in the groups on and not on AP (85.3 % vs 70.9 %, P < 0.0001). There was no statistical difference in post-DBE bleeding rates in patients on AP vs not on AP at 60 days (11.5 % vs 7.5 %, P = 0.12) or 1 year (19.9 % vs 15.7 %, P = 0.23). Rates of bleeding in patients on AC were 11.6 % within 60 days and 22.5 % within 1 year. Multivariate analysis reflected American Society of Anesthesiologist > 3 and indication for DBE of GI bleeding were independent risk factors for post-DBE bleeding within 1 year.Conclusions Continued antiplatelet use at the time of DBE was not an independent risk factor for bleeding post-DBE at 60 days or 1 year of follow up.